Aggressive Surgical Resection of Enormous Cervical Metastasis from Nasopharyngeal Carcinoma - Sha Fu (Acta Stomatologica Croatica, 2019)
While nasopharyngeal carcinoma (NPC) commonly presents lymphoid metastases, the enormous cervical metastasis causing dysphagia and limitation of neck motion is not a familiar symptom for most of NPC cases. We report a 23-year-old male with undifferentiated carcinoma of the nasopharynx, stage Ⅲ (T3N2M0), who had undergone aggressive surgical resection of bilateral huge cervical mass first followed by concurrent chemo-radiotherapy with cisplatin-based regimens. The postoperative clinical course was uneventful and follow-up, 2 years later, revealed no recurrence of primary lesion and neck metastases. We recommend that aggressive surgical resection may be considered when NPC patients significantly suffer clinical symptoms from a huge cervical metastasis.